2021
DOI: 10.1002/chem.202101753
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Photocatalyzed Hydrosilylation of Alkynes and Alkenes under Continuous Flow

Abstract: Herein, the photocatalytic hydrosilylation of alkynes and alkenes under continuous flow conditions is described. By using 0.2 mol % of the developed [Cu(dmp)(XantphosTEPD)]PF6 under blue LEDs irradiation, a large panel of alkenes and alkynes was hydrosilylated in good to excellent yields with a large functional group tolerance. The mechanism of the reaction was studied, and a plausible scenario was suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 53 publications
1
23
0
2
Order By: Relevance
“…Very recently, Poisson et al. used a unique copper catalyst as a photoredox catalyst to generate a silyl radical from a silylboronate by continuous flow . Shibata et al .…”
mentioning
confidence: 99%
“…Very recently, Poisson et al. used a unique copper catalyst as a photoredox catalyst to generate a silyl radical from a silylboronate by continuous flow . Shibata et al .…”
mentioning
confidence: 99%
“…Copper complexes were found to be more efficient, with homoleptic diimine complexes PC 5 and PC 7 15 promoting the reaction, with modest efficiencies however, as with heteroleptic diimine/diphosphine complex PC 6 . 16 [Cu(bcp)DPEPhos]PF 6 PC 8 was found to be the most efficient catalyst, perfluoroalkylated benzofuran 3a being formed in 61% NMR yield. Further evaluation of the catalytic loading, solvent, dilution, reaction time and amount of base did not bring significant improvements while screening a set of inorganic bases enabled a slight improvement when using potassium acetate (65% NMR yield, 66% isolated yield).…”
mentioning
confidence: 99%
“…Copper complexes were found to be more efficient, with homoleptic diimine complexes PC 5 and PC 7 15 promoting the reaction, with modest efficiencies however, as with heteroleptic diimine/diphosphine complex PC 6 . 16 [Cu(bcp)DPEPhos]PF 6 PC 8 was found to be the most efficient catalyst, perfluoroalkylated benzofuran 3a being formed in 61% NMR yield.…”
mentioning
confidence: 99%
“…A final H abstraction resulted in the formation of the hydrosilylated product. With regard to this final H-abstraction and taking into account the labeling experiments and the previous studies from our group, we suggested that the H atom comes from the O–H bond of the methanol. However, taking into account the high bond dissociation energy of this bond, a possible coordination of the latter to a boron species (i.e., a Lewis acid center) might decrease the bond dissociation energy of the O–H bond and therefore allow the H abstraction by the radical IV .…”
mentioning
confidence: 68%